The Evidence for and from Accreditation - Kaye Bender (Georgia Southern University, 2016)
Background: Public health department accreditation administered by the Public Health Accreditation Board (PHAB) began in 2007 after a series of policy briefs, field demonstration initiatives, and completion of a national feasibility study. Methods: Evidence for accreditation was gathered from both national and state-based standards that had been tested and evaluated. Evidence from accreditation was obtained from surveys and focus groups. Results: Preliminary analyses have indicated that the accreditation program is having its intended impact, although longitudinal analyses are planned for the future when a larger number of health departments can respond to surveys over time. Conclusions: PHAB will continue to utilize long-term evaluation methods to describe the long-term impact of the accreditation process on health department performance.